Sports betting : how people bet on sports - Nosal, Przemysław (Routledge, 2025)
This is the first book to focus on sports betting from a sociological perspective. Drawing on multi-stage sociological research, it deepens our understanding of an increasingly significant aspect of the contemporary sport industry.The book examines how bettors engage in sports betting - why they perceive it to be attractive, what betting represents to them and how they know how to bet or how they do so - describing the social phenomenon of betting and placing it within a broader cultural context. Drawing on original empirical research, it uses a practice theory that makes it possible to see in the actions of individuals both the influence of and the impact they have on culture, lifestyle and technology. With sports betting an increasingly controversial subject in wider society, this analysis helps us to understand betting as a complex phenomenon with connections to other areas of social life and how to better understand its impacts and how to mitigate its potential social harms.This is a fascinating read for anyone with an interest in the sociology of sport, sport business, economy, psychology, gambling, sociology, cultural studies, social anthropology or social policy.
Keywords: Sports betting.; Gambling -- Social aspects.; Gamblers -- Psychology.; elektronické knihy; electronic books